Diffusion tensor imaging MRI of sickle cell kidney disease: initial results and comparison with iron deposition. (19th January 2018) - Donnola, Shannon B.; Piccone, Connie M.; Lu, Lan; Batesole, Joshua; Little, Jane; Dell, Katherine M.; Flask, Chris A.
Abstract : Chronic kidney disease (CKD) occurs in over one‐third of patients with sickle cell disease (SCD) and can progress to end‐stage renal disease. Unfortunately, current clinical assessments of kidney function are insensitive to early‐stage CKD. Previous studies have shown that diffusion magnetic resonance imaging (MRI) can sensitively detect regional renal microstructural changes associated with early‐stage CKD. However, previous MRI studies in patients with SCD have been largely limited to the detection of renal iron deposition assessed by T 2 * relaxometry. In this pilot imaging study, we compare MRI assessments of renal microstructure (diffusion) and iron deposition ( T 2 *) in patients with SCD and in non‐SCD control subjects. Diffusion tensor imaging (DTI) and T 2 * relaxometry MRI data were obtained for pediatric ( n = 5) and adult ( n = 4) patients with SCD, as well as for non‐SCD control subjects ( n = 10), on a Siemens Espree 1.5‐T MRI scanner. A region‐of‐interest analysis was used to calculate mean medullary and cortical values for each MRI metric. MRI findings were also compared with clinical assessments of renal function and hemolysis. Patients with SCD showed a significant decrease in medullary fractional anisotropy (FA, p = 0.0001) in comparison with non‐SCD subjects, indicative of microstructural alterations in the renal medulla of patients with SCD. Cortical and medullary reductions in T 2 * (increased iron deposition, p = ≤0.0001) were also observed. Significant correlations were also observed between kidney T 2 * assessments and multiple measures of hemolysis. This is the first DTI MRI study of patients with SCD to demonstrate reductions in medullary FA despite no overt CKD [estimated glomerular filtration rate (eGFR) > 100 mL/min/1.73 m 2 ]. These medullary FA changes are consistent with previous studies in patients with CKD, and suggest that DTI MRI can provide a useful measure of kidney injury to complement MRI assessments of iron deposition. Abstract : Chronic kidney disease (CKD) occurs in over one‐third of patients with sickle cell disease (SCD), but is not easily detected in the early stages. Previous studies have shown that diffusion tensor imaging (DTI) can sensitively detect medullary microstructural changes associated with early‐stage CKD, but have not been studied in patients with SCD. In this pilot magnetic resonance imaging (MRI) study, we show that medullary fractional anisotropy as measured by diffusion tensor imaging (DTI) is significantly reduced in pediatric and adult patients with SCD in comparison with control subjects.